Faktor-faktor yang Memengaruhi Ekspor Kertas dan Barang Berbahan Kertas di Indonesia Periode Tahun 1988-2012 - Cahyadi, Ni Made Ayu Krisna; Sukarsa, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 1, Januari 2015 (pp. 1 - 70), 2015)
Oil export shows a positive trend on contributing in the foreign exchange reserves. Non-oil export consists of agricultural sector, industry, mining and others. There are several excellent industrial products, paper and goods made from paper is one of them. Indonesia successfully became the net exporter of paper on 1987 and in 1996 was ranked to the world’s seventh largest exporter of paper. The purpose of this study are to determine the impact of the US dollar exchange, production, and dummy variable dumping charges simultaneously and partially to the Indonesia’s paper and goods made from paper export and to determine which independent variable has dominant influence on Indonesia’s paper and goods made from paper export in 1988-2012. The result of analysis show that US dollar exchange, production, and dumping charges have simultaneously significant impact to Indonesia’s paper and goods made from paper export. Partially, US dollar exchange and production have positive and significant impact to Indonesia’s paper and goods made from paper while dumping charges has negative and significant impact to Indonesia’s paper and goods made from paper export in 1988-2012. The most dominant variable that influent Indonesia’s paper and goods made from paper export in 1988-2012 is production.
Keywords: paper export, US dollar exchange, production, dumping charges